2020
DOI: 10.1186/s12888-020-2467-y
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Japanese version of the INSPIRE measure of staff support for personal recovery in community mental health service users in Japan

Abstract: Background: Supporting personal recovery in people with mental health difficulties is central to mental health services. This study aimed to develop the Japanese version of INSPIRE and Brief INSPIRE measure of staff support for personal recovery and to evaluate its reliability and validity. Methods: A questionnaire survey was conducted from October to December 2015. The authors asked users to participate in the survey of 14 community mental health services in the Kanto region of Japan. The service users comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The other nine scales were patient-reported outcome measures. Two were recovery-related scales (Japanese version of the Questionnaire about the Process of Recovery (QPR-J) [24][25][26] and INSPIRE [27,28]). The remaining seven scales included the domains for empowerment (Japanese version of Boston University Empowerment Scale (BUES)) [29][30][31], quality of life (QOL)/well-being (WHO-5) [32,33], social support (Japanese version of the Social Support Questionnaire -Short Form (SSQ-6)) [34,35], subjective value (Japanese version of the Personal Values Questionnaire II (PVQ-II)) [36], relationships between patients and clinicians (Japanese version of the Scale to Assess Therapeutic Relationships (STAR-J)) [37,38], self-stigma (Japanese version of the Internalized Stigma of Mental Illness (ISMI) scale) [39,40], and adherence (Medication Adherence Scale) [41].…”
Section: List Of Outcome Measuresmentioning
confidence: 99%
“…The other nine scales were patient-reported outcome measures. Two were recovery-related scales (Japanese version of the Questionnaire about the Process of Recovery (QPR-J) [24][25][26] and INSPIRE [27,28]). The remaining seven scales included the domains for empowerment (Japanese version of Boston University Empowerment Scale (BUES)) [29][30][31], quality of life (QOL)/well-being (WHO-5) [32,33], social support (Japanese version of the Social Support Questionnaire -Short Form (SSQ-6)) [34,35], subjective value (Japanese version of the Personal Values Questionnaire II (PVQ-II)) [36], relationships between patients and clinicians (Japanese version of the Scale to Assess Therapeutic Relationships (STAR-J)) [37,38], self-stigma (Japanese version of the Internalized Stigma of Mental Illness (ISMI) scale) [39,40], and adherence (Medication Adherence Scale) [41].…”
Section: List Of Outcome Measuresmentioning
confidence: 99%
“…The Principal Axis Factor analysis with oblimin rotation (25) and varimax rotation methods were adopted for EFA. The number of factors was determined by eigenvalues and scree plots using an eigenvalue criterion higher than 1 (26).…”
Section: Factor Analysismentioning
confidence: 99%
“…The INSPIRE was originally developed in the United Kingdom and has two subscales, "Support" and "Relationship" (Williams et al, 2015). Previous research reported that the Japanese version of the INSPIRE had good reliability and convergent validity (Kotake et al, 2020). A higher score indicates that the participant more strongly agrees that they have been receiving recovery-oriented services and have built a good relationship with an employment specialist.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%